Digital Marketing in Agriculture: Perception and Decision Making of Apple Farmers in Bumiaji, Batu City - Kholifa, Umi Nur; Yuliati, Nuriah; Atasa, Dita (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
The difference in farmers' perceptions of using digital marketing as a marketing strategy indicates that not all farmers share the same views, understanding, and readiness to adopt such technology. This study aims to analyze the perceptions of farmers who use and do not use digital marketing, and to examine the factors influencing farmers' decision-making in adopting digital marketing. The research was conducted in Tulungrejo Village, Bumiaji District, Batu City. The research method used was a quantitative approach. The sample consisted of 90 farmers, divided into two categories: 54 farmers who use digital marketing and 34 who do not. The first objective was analyzed using descriptive quantitative analysis with a Likert scale, while the second objective was examined using binary logistic regression. The results showed that farmers’ perception of digital marketing scored an average of 4.15, categorized as high. The variables of age, motivation, social support, and access to technology significantly influenced farmers’ decisions to use digital marketing, each with a significance value below 0.05. Meanwhile, the variables of education level, farming duration, farming experience, cost, and resource availability did not significantly affect the decision to use digital marketing.